2013
DOI: 10.1007/s00595-013-0528-2
|View full text |Cite
|
Sign up to set email alerts
|

Impact of cardiac stem cell sheet transplantation on myocardial infarction

Abstract: The 3-layered cell-sheet improved cardiac function associated with angiogenic and anti-fibrotic effects. Thus, CSC is a promising cell-source to use with the cell-sheet method for the treatment of cardiac failure, as long as a sufficient number of cells are delivered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 20 publications
0
14
0
Order By: Relevance
“…This xenotransplantation model has been used in a number of studies, which have rarely reported significant immunological reactions. 22, 35 In fact, the transplanted cells in this study were not histologically involved in inflammatory reactions such as accumulation of inflammatory cells (data not shown). Thus, immune rejection in this model is minimal and does not affect the results.…”
Section: Matsuda T Et Al Different Results For In Vitro and In Vivo mentioning
confidence: 64%
“…This xenotransplantation model has been used in a number of studies, which have rarely reported significant immunological reactions. 22, 35 In fact, the transplanted cells in this study were not histologically involved in inflammatory reactions such as accumulation of inflammatory cells (data not shown). Thus, immune rejection in this model is minimal and does not affect the results.…”
Section: Matsuda T Et Al Different Results For In Vitro and In Vivo mentioning
confidence: 64%
“…Nevertheless, the outcomes of clinical studies on stem cell transplantation vary and point to little long-term benefit [130]. New approaches are therefore being applied in experimental models, including cell-sheet transplantation [131,132], gene modification of stem cells [11,133], and co-delivery of stem cells with pro-angiogenic growth factors [13]. Recently, apelin, a critical enhancer of angiogenesis, was reported to be reduced in patients after MI [20] while lower apelin level had an inhibitory effect on vascular sprouting and myocardial angiogenesis [20].…”
Section: Discussionmentioning
confidence: 99%
“…The cell sources for sheet used in cardiac transplantation to damaged hearts with MI in animal models include fibroblasts [33,34], endothelial cells [35], cardiomyocytes cocultured with endothelial cells [35], dermal fibroblasts cocultured with endothelial progenitor cells [33], SMs [36][37][38][39][40][41], mesenchymal stem cells from adipose tissue [42,43], bone marrow [44,45], menstrual blood [46], adipocytes [47], adipose-derived stem cells [42,43], cardiomyocytes from neonatal animals [34], Sca-1 (+) CPCs and Ckit (+) CPCs from adult murine hearts [48,49], and ESC/ iPSC-derived pure cardiomyocytes [50] or multiple cardiac cell lineages composed of cardiomyocytes and vascular cells [51,52]. Collectively, considering their benefits and further perspectives of clinical application, we reviewed research updates about the use of SM-, MSC-, and ESC/ iPSC-CM-derived cell sheet in MI therapy in this current paper.…”
Section: Stem Cell Composition Of Cell Sheetmentioning
confidence: 99%